Creativity of Contemporary Education in Elementary Schools Through Introduction to Animal Shape from Dry Leaf Materials (Global Scientific Review, 2022)
School-Based Quality Improvement Management is a management model that provides higher autonomy to schools, flexibility, and encourages the direct participation of school members and the community to improve the quality of schools based on national education policies and applicable laws and regulations. Garbage waste in the form of dry leaves which is often considered to have no value can actually be transformed into a work of art as well as an effective creative learning media. In implementing this project the method used was the observation method which took place at SDN 43 Hulonthalangi, Gorontalo City. Students observe the material that has been provided, they are free to imagine according to their observations. Their answers varied, some answered insects, butterflies, dragonflies and beetles. The results of the research by sticking, cutting, and making patterns in forming the animals around us.